Pengembangan Leaflet Digital Tema Makananku Kesehatanku untuk Menumbuhkan Kemampuan Berpikir Kritis Siswa SMP - Nurdayanti, Nurdayanti; Dwi Indah Suryani; R. Ahmad Zaky El Islami (PENDIPA Journal of Science Education, 2023)
According to the results of interviews conducted at junior high schools in the Lebak area, learning activities aimed at developing students’ critical thinking skills have not been carried out properly. For this reason, teaching resources that can be used are digital leaflet teaching materials. This study animed to obtain the feasibility and legibility of digital leaflets with the topic "my food, my health" which is oriented toward the critical thinking skills of grade VIII junior high school students. The research methodology used was Research and Development, limited according to the abilities and needs of researchers, namely using three stages: define, design, and develop stages. A questionnaire instrument sheet is a tool used for investigation, which will be assessed by material validators, media, and practitioners, as well as readability by students with quantitative descriptive and qualitative descriptive data analysis. The findings of this study indicate that digital leaflets with the topic "My food, my health" can be used to help grade VIII students of junior high school develop critical thinking skills that based on media validation, scored 87.5% in the "very appropriate" category, while material validation scored 93.45% in the "very feasible" category, while practitioner validation obtained a score of 89.22% in the "very appropriate" category and readability students get a score of 91.88% with very good category.